The Impact of Industry 4.0 on Women-Owned Agribusinesses in South Africa- Gauteng Province - Cebekhulu-Msomi, Phindile; Singh, Shamila (Sustainability Science and Resources, 2025)
Women-owned agribusinesses in Gauteng, South Africa face significant challenges in leveraging Industry 4.0 technologies for sustainable growth to understand the influence on business expansion and profitability to design targeted interventions.This study examines the impact of Industry 4.0 on women-owned agribusinesses in Gauteng, South Africa, using a survey of 135 female farmers to identify key factors and strategies for growth. A survey was distributed through Google Forms to gather quantitative data from 135 female farmers. Descriptive and inferential statistics, including Spearman's rank correlation and ordinal regression, were used to analyse the data. The study found that women-owned agribusinesses face significant financial challenges, with 48.1% reporting losses or no profit in 2022 compared to 2018. Only 9.6% of businesses reported gross profits above R200,000, indicating that very few women-owned agribusinesses were able to reach high profitability levels. The study also found that funding, market accessibility, and agricultural skills are the three most important factors for business expansion, with 73.3% of participants considering funding extremely important. Additionally, the study found a weak positive correlation between the use of Industry 4.0 technology and gross profit margins, suggesting that technology adoption is important but not the primary driver of profitability. Women-owned agribusinesses in Gauteng face significant financial difficulties, with a majority reporting losses or low profitability. Tailored interventions considering demographic factors and leveraging the potential of technology are needed for sustainable growth. The study provides valuable insights into the challenges and opportunities faced by women-owned agribusinesses to navigate the impact of Industry 4.0. The findings highlight the importance of focused support in areas like funding, market access, and skill development to improve the expansion and sustainability of these businesses. Key Words: Food security, Industry 4.0, Sustainable Growth, Technology Adoption, Women-owned agribusinesses, Economic empowerment, Smart technologies, Automation